Seasonal Variations of copper and lead bio-accumulation in two fish species: Mullus barbatus and Siganus rivulatus in the southern part of the Syrian Coast - Soliman, Yana; Saad, Adib A.; Hammoud, Vienna (Iraqi Journal of Aquaculture, 2023)
Seasonal variations in the concentrations of two heavy metals: copper (Cu) and lead (Pb) were determined in the liver and muscles of Mullus the two species barbatus and Siganus rivulatus fish from the southern part of Syrian Coast. The average concentrations of the metals in the fish tissues exhibited the following order: Cu>Pb. The statistical analysis revealed a significant seasonal effect P≤0.05 for Cu and Pb measured. The highest values of the metals were recorded in dry season. The highest concentrations of heavy metals were found in liver tissue of both fish species, while the lowest concentrations were recorded in muscles tissue. The values of the metals detected in the fish muscles (the edible part) were within the permissible limits